In vitro and in vivo biocompatibility, bioavailability and tolerance of an injectable vehicle for adipose-derived stem/stromal cells for plastic surgery indications. Issue 11 (November 2015) - Lequeux, Charlotte; Rodriguez, Jonathan; Boucher, Fabien; Rouyer, Ondine; Damour, Odile; Mojallal, Ali; Auxenfans, Céline
Summary: Soft tissue reconstruction is a challenge in plastic surgery, when replacing lost materials and correcting contour defects. Many permanent and temporary fillers have been used to restore the volume of these lesions, but often with poor results and even complications. Adipose-derived stem/stromal cells (ASCs) and adipose tissue engineering have been suggested as valuable alternatives. In order to inject these cultured cells, it was essential to find a suitable vehicle. The purpose of this study was to evaluate Cytocare ®, an injectable medical device, composed of hyaluronic acid plus amino acids, vitamins and mineral salts. First, ASC viability and bioavailability in the 3 different available Cytocare ® formulations using the MTT test were assessed; then an animal experiment, testing the tolerance after intradermal injections of both Cytocare ® alone and with ASCs was carried out. Our in vitro results demonstrate a high biocompatibility of Cytocare ® resulting in a better viability of ASCs when cultured in Cytocare ® compared to culture medium (p < 0.05, Mann and Whitney). Cytocare ® also permits their bioavailability and proliferation, making it a potential transfer vehicle that can retain the cells before their integration around the recipient site. Finally, our animal experiment shows that the ASC + Cytocare ® combination is well tolerated. In conclusion, Cytocare ® can be used as a biocompatible scaffold for cultured ASCs in therapeutic treatments, ensuring ASC bioavailability, as well as evidence of excellent tolerance in nude mice.